Pola Mobilitas Penduduk Kawasan Pinggiran Kota Baubau: (Studi Pada Kec. Betoambari Dan Kec. Wolio) - Muumin Muuzi; Batara Surya; Kamran Aksa (Fakultas Teknik Universitas Bosowa, 2020)
This study aims to analyze the comparison of patterns of population mobility in the suburban of Baubau and analyze the influence of mobility patterns against the pattern of Baubau suburban area. This research uses qualitative and quantitative approach method with analysis technique used is qualitative descriptive, gravity model, connectivity index and path analysis. The results showed that the pattern of mobility of the population in the suburban baubau has no significant difference because the average population moves in the morning for the purpose of working with the mode of transportation used is a private vehicle of two wheels / motors where distance factors and transportation costs are the main reason for choosing the mode of transportation used. The result of gravity analysis shows that Kec. Wolio has a value of large spaces and interdependence for each zone that is the destination of movement in the city center compared to Kec. Betoambari. Furthermore, the results of the path analysis shows that the movement of the movement and transport mode has a significant effect on the pattern of the activities of the Burau Supreme Territory, while the socio-economic attribute, the time of movement and socioeconomic activity has no significant direct influence. For the effect of unanshipless significantly influenced by the movement system and the mode of transportation and indirect influence is not significantly influenced by socio-economic attributes and the time of movement.